INFLUENCE COMPANY SIZE, CAPITAL STRUCTURE, DIVIDEND POLICY ON FINANCIAL PERFORMANCE WITH BIODIESEL PRODUCTION AS MODERATING VARIABLES IN PALM OIL PROCESSING COMPANIES ON THE INDONESIA STOCK EXCHANGE (IDX) - Winarsih Winarsih; Yulia Efni; Andewi Rokhmawati (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study aims to determine and analyze firm size, capital structure, dividend policy on the company's financial performance. To analyze biodiesel production strengthen the relationship between firm size, capital structure, dividend policy and company financial performance. The population in this study is the use of company data included in the palm oil processing sector companies that went public on the Indonesia Stock Exchange (IDX) in the period 2014 to 2019. The sample in this study was 12 companies that met the sampling characteristics that have been determined. The analytical technique used in this research is PLS Structural Equation Modeling (SEM) which is operated through the WarpPLS.5.0 program. The results of the study show that the size of the company and capital structure on financial performance. Dividend policy has no effect on financial performance. Company size, capital structure have a significant effect on financial performance with Biodiesel Production as a Moderating Variable. The results of financial research on dividend policy have no effect on company performance with biodiesel production as a moderating variable